Peran Guru sebagai Konselor dalam Mengatasi Masalah Belajar Siswa di MAN 1 Banjarmasin - Naimah Naimah (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2023)
The purpose of this article is to find out the learning problems faced by students at MAN 1 Banjarmasin, how the teacher's efforts are being taken in overcoming these problems. The method used is qualitative-descriptive, the research found; (1), students experience difficulties in solving assignments and material problems provided by the teacher. The problem factors that occur come from the students themselves. (2) Efforts made by teachers in schools that experience learning problems, namely maximizing their sense of hearing by listening to the teacher when explaining learning material, being guided when children do not understand the learning material and the latter is directed when children do not pay attention to the teacher explaining material in the learning process. Third, the teacher's stages in overcoming student learning problems starting from determining.